A variation in SORBS1 is associated with type 2 diabetes and high‐density lipoprotein cholesterol in Chinese population. Issue 5 (20th February 2022) - Gong, Siqian; Huo, Shaofeng; Luo, Yingying; Li, Yufeng; Ma, Yumin; Huang, Xiuting; Hu, Mengdie; Liu, Wei; Zhang, Rui; Cai, Xiaoling; Zhou, Lingli; Chen, Ling; et al.
Abstract: Aim: Sorbin and SH3‐domain‐containing‐1 (SORBS1) play important roles in insulin signalling and cytoskeleton regulation. Variants of the SORBS1 gene have been inconsistently reported to be associated with type 2 diabetes or diabetic kidney disease (DKD). Methods: Two independent case‐control studies based on two randomized sampling cohorts (cohort 1, n = 3345; cohort 2, n = 2282) were used to confirm the association between rs2281939 of SORBS1 and impaired glucose regulation (IGR). An additional hospital‐based cohort (cohort 3, n = 2135) and cohort 1 were used to investigate the association between rs2281939 and DKD. The phenotype of rare variants of SORBS1 was explored in 453 patients with early onset type 2 diabetes (diagnosed before 40 years of age, EOD). Results: The G allele was associated with type 2 diabetes (additive model: OR = 1.25, 95% CI [1.03–1.52], p = 0.022) in cohort 1, and IGR in cohort 2 (additive model: OR = 1.22, 95% CI [1.05–1.43], p = 0.01). We found that the G allele was also associated with HDL‐c levels in women in both cohort 1 ( p = 0.03) and 2 ( p = 0.029) in the dominant model. The rare variant carriers also had lower HDL‐c and LDL‐c levels than non‐carriers in patients with EOD. No association between rs2281939 or rare variants and DKD was observed. Conclusions: The variants in the SORBS1 gene were associated with IGR and HDL‐c levels but not with DKD in the Chinese Han population.